2018
DOI: 10.1111/php.12994
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Mechanism of Nicotinamide Against UVA‐ and/or UVB‐mediated DNA Damages in Normal Melanocytes

Abstract: Melanoma incidences are increasing rapidly, and ultraviolet (UV) radiation from the sun is believed to be its major contributing factor. UV exposure causes DNA damage in skin which may initiate cutaneous skin cancers including melanoma. Melanoma arises from melanocytes, the melanin-producing skin cells, following genetic dysregulations resulting into hyperproliferative phenotype and neoplastic transformation. Both UVA and UVB exposures to the skin are believed to trigger melanocytic hyperplasia and melanomagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 31 publications
(39 reference statements)
0
21
0
Order By: Relevance
“…The transcriptional regulation of the antioxidant defense system is promoted by the Nrf2-Antioxidant Response Element (ARE) signaling pathway which stimulates the expression of phase II detoxification enzymes including glutathione reductase (GR), heme oxygenase-1 (HO-1), catalase (CAT), manganese superoxide dismutase (MnSOD), and copper zinc superoxide dismutase (CuZnSOD) [14]. In addition, DNA damage induced by UVB irradiation is associated with Nrf2-regulated antioxidants responses in skin cells [15,16]. Thus, synthetic compounds, in particular free radical scavengers or natural products targeting Nrf2, have been proposed to be used in skin photoprotection [1,15,[17], [18], [19], [20]].…”
Section: Introductionmentioning
confidence: 99%
“…The transcriptional regulation of the antioxidant defense system is promoted by the Nrf2-Antioxidant Response Element (ARE) signaling pathway which stimulates the expression of phase II detoxification enzymes including glutathione reductase (GR), heme oxygenase-1 (HO-1), catalase (CAT), manganese superoxide dismutase (MnSOD), and copper zinc superoxide dismutase (CuZnSOD) [14]. In addition, DNA damage induced by UVB irradiation is associated with Nrf2-regulated antioxidants responses in skin cells [15,16]. Thus, synthetic compounds, in particular free radical scavengers or natural products targeting Nrf2, have been proposed to be used in skin photoprotection [1,15,[17], [18], [19], [20]].…”
Section: Introductionmentioning
confidence: 99%
“…The transcriptional regulation of the antioxidant defense system is promoted by the Nrf2-Antioxidant Response Element (ARE) signaling pathway which stimulates the expression of phase II detoxification enzymes including glutathione reductase (GR), heme oxygenase-1 (HO-1), catalase (CAT), manganese superoxide dismutase (MnSOD), and copper zinc superoxide dismutase (CuZnSOD) [14]. In addition, DNA damage induced by UVB irradiation is associated with Nrf2-regulated antioxidants responses in skin cells [15,16]. Thus, synthetic compounds, in particular free radical scavengers or natural products targeting Nrf2, have been proposed to be used in skin photoprotection [1,15,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnology-based cosmetics 6 , and new ingredients with anticancer 7 , antioxidant 8 , and anti-inflammatory properties 9 have been introduced into cosmetic products to prevent and/or treat skin diseases. Recently, a few studies have demonstrated the effect of specific compounds e.g., naproxen 10 , silver nanoparticles 11 , nicotinamide 12 , etc., on the prevention of UVB-induced skin cancers. The possible toxicity of chronic application of these compounds on the skin limits their routine administration as daily applied cosmeceuticals such as sunscreens.…”
Section: Introductionmentioning
confidence: 99%